Simulation Study of a Vehicle Production Line for Productivity Improvement - M. F. F., Ab Rashid; N. M. Zuki, N. M.; A. N., Mohd Rose (Faculty Mechanical Engineering, UMP, 2015)
This paper presents the study of a motorcycle frame production line in a particular company in Malaysia. Due to the high demand, the company needs to increase its production by at least 12% compared with current output. In order to improve productivity, the production-floor data was collected and simulated using the discrete event simulation approach. Later, a number of suggestions for improvement were simulated to identify the effect of the suggestions on productivity. In addition, cost analysis was also undertaken to identify the profit margin for a particular period of time for each suggestion. Simulation results indicate that there are three suggestions that are able to fulfill the 12% volume increment. In the short term, the suggestion to hire an assistant line leader will give instant effect to the profit. Meanwhile, for the medium term, Poka-yoke will give higher profit compared with the others, while in the long term, SOP (standard operating procedure) implementation will yield a better profit margin. In future, the simulation of a dynamic demand model for this product is suggested to cope with new trends in the market.